Metagenomic analysis post thermal stress in buffalo sludge and tomato pomace anaerobic digestion: a case study - Maria Chiara La Mantia (Revista Científica)
The tomato processing industry is one of the most important sectors in the agri-food industry, and annually,  more than 39.2 million tons of tomatoes are processed globally. Italy is the first producer of processed tomato es in the Mediterranean area and the third-largest producer in the world. Buffalo farming represents a relevant sector within Italian agriculture, and one of its main issues is manure management. Both economic activities generate a substantial amount of waste (buffalo sludge - BS and tomato pomace – TP, peels plus seeds) that can significantly impact the disposal costs and, hence, their economic and environmental sustainability. The case study followed the evolution of microflora composition during anaerobic co-digestion of BS and TP for biogas production (Inoculum/Substrate ratio 0.5 according to volatile solid content) under mesophilic conditions (39°C) using an Automatic Methane Potential Test System, before and after a thermal stress (three-day period at 50 °C) occurred. BS was used as inoculum and control. The bacterial and archaeal communities were an-alyzed using next-generation sequencing of 16S rRNA gene amplicons. After seven days of fermentation, due to the high volatile solid content in TP (77 g/L), the pH dropped to a value of 5, and the methane production reached a plateau (860 Nml of cumulative CH4 production). After the thermal stress, there was a shift in microbial populations, the pH increased back to neutrality, and the TP batch was able to resume biogas production, reaching 3048 Nml of cumulative CH4 production at the end of fermentation (45 days). A maximum methane peak at 78.5% in BS/TP biogas was recorded compared to 63.5% in BS. Taxonomic classification showed that the bacteria phyla belonging to Firmicutes (51.7%), of whom 47.4% were Clostridia, Bacteroidetes (29.9%) mostly Bacteroidia (29.0%), Tenericutes (4.1%) and Proteobacteria (3.2%), accounted for 88.9% of total OTUs. Among the Clostridiaceae, Fonticella (4.3% on average) was the most represented genus. The latter was absent in the BS sample and increased to 17.1% in the BS/TP sample when methane production was restored, while in the archaeal community predominated the phylum Euryarcheota, with Methano corpusculum being the most represented and Metanosarcina the most correlated to methane production. Brief thermal stress significantly changed bacterial and archaeal populations crucial to increasing methane production at the conditions tested.